Modeling Sorption of Neutral Organic Compound Mixtures to Simulated Aquifer Sorbents with Pseudocompounds. Issue 3 (1st May 2013) - Joo, Jin Chul; Shackelford, Charles D.; Reardon, Kenneth F.
Abstract : The feasibility of the ideal adsorbed solution theory (IAST) in reducing the complexity associated with predicting the sorption behaviors of 12 neutral organic compounds (NOCs) contained in complex mixtures as a fewer number (four to six) of pseudocompounds (groups of compounds) to simulated aquifer sorbents was investigated. All sorption isotherms from individual‐ and multiple‐pseudocompound systems were fit reasonably well ( r 2 ≥ 0.953) by the Freundlich sorption model over the range of aqueous concentrations evaluated (i.e., ≤200 μmol L −1 ). The presence and magnitude of mutual competition among pseudocompounds varied depending on the composition of the mixtures (i.e., concentrations and polarities of pseudocompounds) and the properties of sorbents (i.e., the fraction of organic carbon and the availability of hydrophilic specific sorption sites). Finally, comparisons between the IAST‐based predictions with individual‐pseudocompound sorption parameters and experimentally measured data revealed that the accuracy in predicting the sorption behaviors of several NOCs in terms of a fewer number of pseudocompounds decreased with increasing deviations from the assumption of equal and ideal competition in the IAST (i.e., differential availability of sorption sites and nonideal competitions among pseudocompounds).